Trends in college students' mental health diagnoses and utilization of services, 2009–2015. Issue 1 (2nd January 2020) - Oswalt, Sara B.; Lederer, Alyssa M.; Chestnut-Steich, Kimberly; Day, Carol; Halbritter, Ashlee; Ortiz, Dugeidy
Abstract: Objective : To examine changes in diagnoses/treatment for 12 mental health (MH) conditions, previous use of campus MH services, and willingness to seek MH services in the future. Participants: ACHA–NCHA II participants from 2009 to 2015 ( n  = 454, 029). Methods: Hierarchical binary logistic regression with step 1 controlling for demographics and step 2 considering time. Results: Time was significant except for bipolar disorder, bulimia, and schizophrenia with increases for all conditions except substance abuse. Anxiety (OR = 1.68), panic attacks (OR = 1.61), and ADHD (OR = 1.40) had the highest odd ratios. Use of MH services at current institution (OR = 1.30) and willingness to utilize services in the future (OR = 1.37) also increased over time. Conclusions: Based on a national sample, self-reported diagnoses/treatment of several MH conditions are increasing among college students. This examination of a variety of MH issues can aid college health professionals to engage institutional stakeholders regarding the resources needed to support college students' MH.